Recent advances based on a sensor for cancer biomarker detection - Crulhas, Bruno P. [UNESP]; Basso, Caroline R. [UNESP]; Castro, Gustavo R. [UNESP]; Pedrosa, Valber A. [UNESP] (The Electrochemical Society, 2021)
Cancer is a worldwide disease with a high mortality rate and traditional methods for the diagnosis and monitoring are performed through invasive techniques. Currently, the advance of research in medical and biomedical engineering allowed the use of molecular tools combined with nanotechnology to develop portable sensors specific for major biomarkers to diagnose, monitor, and treatment of several diseases. This sensor can offer a means of homogeneous classification of a disease and risk factor and can extend the basic information about the underlying pathogenesis of the disease. Therefore, they can play a critical role in all stages of the disease. To address all this requirement is important to have a rigorous evaluation, including analytical validation, before incorporated into routine clinical treatment. This review described the current stage in the development of sensors in the study of cancer with an emphasis on surface modification, immobilization of biological agents, and detection approach.